Cardiorespiratory responses to haemolytic anaemia in rainbow trout Oncorhynchus mykiss. Issue 4 (17th August 2015) - Gold, D. K.; Loirat, T.; Farrell, A. P.
<x xml:space="preserve">Abstract</x> To quantify cardiorespiratory response to experimental anaemia in rainbow trout Oncorhynchus mykiss, a 24 h phenylhydrazine treatment was used to reduce haematocrit to almost one third of its initial value over 4–5 days. In response, relative blood velocity in the ventral aorta (an index of cardiac output) progressively increased to more than double to its normocythaemic value and there was no significant change in routine oxygen uptake. Thus, the primary compensatory response to anaemia was an increase in cardiac output.